(untitled) (Eurasian Medical Research Periodical, 2023)
The volume of distribution of HCV and its genotypes among healthy children and adults has been established, as well as different risk groups for the incidence of viral hepatitis living in the hyperendemic zone of the Ferghana Valley have been identified. A high frequency of detection of anti - HCV was revealed. A high level of carriage was noted in the groups of patients in the intensive care unit and human donors